Foreign Investment, State Capitalism, and National Development in Borneo: Rethinking Brunei–China Economic Relations - Lim, Guanie; Hoon, Chang-Yau; Zhao, Kaili (Journal of Current Southeast Asian Affairs, 2023)
Faced with dwindling oil and gas reserves, Brunei has been hard-pressed to diversify its reliance on hydrocarbon. China has emerged as an attractive prospect to the Brunei government, especially since the launch of the Belt and Road Initiative. This article analyses a few major Chinese projects in Brunei and postulates three interrelated arguments. Firstly, Chinese investors have targeted Brunei's natural resources and fiscal incentives. These firms have minimal interest in the Sultanate's small domestic market as they eye the export sector. Secondly, these projects have been orchestrated by China's provincially-owned state-owned enterprises (SOE) and private firms, instead of centrally- controlled SOEs. State support has generally been channelled to these projects in an at-arm's length manner. Thirdly, while Brunei is relatively skilled in attracting Chinese investors to further its own political economic goals, at least in the short-run, it is uncertain whether such capital exports have helped in ameliorating the structural limits of the country’s economy.